Closing-the-loop: a novel care coordination tool to reduce maternal healthcare utilization postpartum and collaboratively build interventions to address community needs - Amanda Terry; Chelsea Arnold; Zackery White; Mary O’Connor; Gillian Feldmeth; Halima Ahmadi-Montecalvo (BMC Pregnancy and Childbirth)
Abstract Background In August 2020, Sarasota Memorial Health Care System (Sarasota Memorial) invested in Unite Us, a closed-loop referral platform, to address obstetric (OB) patients’ non-medical needs. The platform was used to electronically refer patients delivering at Sarasota Memorial who screened positive for these needs to a local network of community-based organizations. Methods A pre-post intervention study with a quasi-experimental, 1:1 matched design was used to measure the impact of implementing a technology-enabled care coordination platform on postpartum health care utilization. Deliveries were matched on patient and birth characteristics including age, race and ethnicity, marital status, insurance type, maternal comorbidities, and birth-specific factors. The impact of the Unite Us platform was assessed using conditional logistic regression, and results were stratified by insurance type, delivery method, low birthweight, preterm delivery, marriage status, infection complications, mental health diagnoses, and race/ethnicity. Results The study consisted of 1,996 deliveries with a live birth, 998 of which were to patients referred for community care through Unite Us from August 27, 2020 to January 31, 2023. These were matched with 998 deliveries with a live birth prior to Unite Us implementation, from January 1, 2019 to August 26, 2020. Matches were predominantly Medicare or Medicaid insured (65.0%), White, Non-Hispanic (56.6%) or Hispanic (28.2%), and never married (62.6%). When stratified by insurance type, patients who were enrolled in Medicaid/Medicare insurance at delivery were 59% less likely (OR: 0.41; 95% CI: 0.17 to 0.99) to be readmitted to the hospital within thirty days of discharge and were 55% less likely (OR: 0.45; 95% CI: 0.21 to 0.99) to have any OB-related inpatient admission within six months of discharge when compared to those who received usual care before Unite Us’ implementation. Conclusions Using the Unite Us platform as a digital tool to advance care coordination, the OB Service line within Sarasota Memorial observed statistically significant reductions in postpartum healthcare utilization in Medicaid/Medicare beneficiaries indicating that addressing non-medical, health-related needs may improve postpartum outcomes and reduce costs. These referral data are also used to facilitate community discussions on ways to build a more supportive network to improve maternal and child health outcomes.